THE INFLUENCE OF THE “ ANAKKU” HEALTH MODULE AS AN EDUCATIONAL MEDIUM FOR MOTHERS WHO HAVE TODDLERS ON THE USE OF KIA BOOKS IN THE KARANGANYAR HEALTH CENTER WORK AREA IN TASIKMALAYA CITY - Tatu Septiani Nurhikmah; Meti Patimah; Alpia Sugandi (Universitas Muhammadiyah Kudus, 2023)
The low participation of the community and the lack of health facilities greatly affect the information and education function of kia books. in order for health information to be accepted by all residents in various regions, there needs to be a role for the community, especially mothers of babies and toddlers. this child health module helps midwives educate toddler mothers.The purpose of this study is to find out the influence of child health modules as an educational medium for mothers who have toddlers on the use of kia books. the study used a quasi-experimental method with the group's pre- and post-test approaches. the primary data type, population and sample of all mothers who have toddlers in the new coral health center of tasikmalaya city as many as 720 people. criteria for inclusion of mothers who have kia books, can communicate well, are willing to be respondents. the samples in this study used simple random sampling techniques. the data obtained is then processed reliability measurement reliability test using cronbach alpha. a variable is said to be reliable if it gives a cronbach alpha value of 0.7. hypothesis analysis test using paired test. there is an influence of providing education using the child health module with the use of kia books by mothers who have toddlers p value 0,000. the results of this study are expected that health workers always provide education for toddler mothers when going to posyandu and conducting a comfort check with the guidance in the kia book.